Alterations in VKORC1 Gene and Cardiac Enzymes in Acute and Chronic Congestive Heart Failure - Dhuha Abdullah Abbas (Journal La Lifesci, 2026)
disorder that activates compensatory mechanisms, including neurohormonal responses and circulatory adjustments, which initially preserve perfusion but later contribute to systemic and pulmonary congestion. This study examined the effect of acute and chronic CHF on VKORC1 gene overexpression and measured serum cardiac enzymes, namely troponin I (cTn I), creatine kinase MB (CK MB), lactate dehydrogenase (L LDH), and myoglobin (MYO MB), at each disease phase. The study included 40 CHF patients, consisting of 20 with acute CHF (ACHF) characterized by severe sudden cardiac symptoms and 20 with chronic CHF (CCHF) showing gradual progression, along with 20 healthy participants as a negative control group. Venous blood samples were collected for molecular analysis using quantitative PCR and for serological assessment of cardiac enzymes using quantitative ELISA. Statistical significance was determined using GraphPad Prism at p < 0.05. The results showed that, across all groups, the GG genotype frequency was significantly higher than GA and AA. However, allele frequency analysis of VKORC1 (-1639G>A) rs9923231 revealed significantly increased GA and AA frequencies in both ACHF and CCHF patients. Serologically, cTn I, CK MB, L LDH, and MYO MB levels were significantly elevated in both patient groups compared with controls. Between ACHF and CCHF, only CK MB was significantly higher in CCHF, while cTn I, L LDH, and MYO MB showed no significant difference. This appears to be the first Iraqi study linking VKORC1 with CHF phases, suggesting its potential as an indicator of both acute and chronic CHF, although further investigation is needed